ANALISIS EFEKTIVITAS PENGGUNAAN BAHAN KOAGULAN DALAM PENGOLAHAN AIR BERSIH DI IPA V SOMBA OPU SERTA DAMPAKNYA PASCA LONGSOR GUNUNG BAWAKARAENG - Arsyad Arsyad (Yayasan Nusantara Hasana Berdikari, 2026)
The availability of clean water is a fundamental need for urban communities, which continues to increase with population growth. The Somba Opu V Water Treatment Plant (IPA) in Gowa Regency plays a vital role in supplying clean water to most areas of Makassar City, with a production capacity of 1,000 liters/second. This study aims to analyze the effectiveness of the use of coagulants in the clean water treatment process at the Somba Opu V IPA and to evaluate the impact of the 2004 Mount Bawakaraeng landslide on raw water quality. The research method used a qualitative descriptive approach with time series and cross-sectional data analysis from laboratory test results. The results showed a drastic increase in raw water turbidity from an average of 45 NTU to 1,214 NTU after the landslide, with a peak turbidity reaching 217,000 NTU, which led to the shutdown of the IPA. Evaluation of coagulant effectiveness showed that the use of Alum and PAC resulted in excessive sludge and high operational costs, while Magnaflo LT27 and LT525 coagulants proved more effective at an affordable price and significantly reduced turbidity. This study concluded that water treatment effectiveness is highly dependent on selecting a coagulant that matches the turbidity characteristics of the raw water, and that treatment system development and infrastructure rehabilitation are necessary to improve the quality of the resulting clean water.